Comparison of Survival Prediction with Single versus Combination Use of Microcirculation End Point Resuscitation in Sepsis and Septic Shock - Robert Sinto; Suhendro Suwarto; Djoko Widodo (Acta Medica Indonesiana)
Background: lactate clearance and central venous oxygen saturation (ScvO2) are two methods for determining tissue oxygenation adequacy. There is a controversy regarding method better associates with and predicts sepsis and septic shock patients’ mortality. This study address the association of achieving one or two targets of microcirculatory resuscitation endpoints and early mortality in sepsis and septic shock. Methods: a cohort study was conducted in adult sepsis and septic shock patients in Intensive Care Unit, Cipto Mangunkusumo Hospital, Indonesia. Patients’ resuscitation endpoints data and outcome were observed during the first 120 hours of hospitalization. Cox’s proportional hazard regression analysis was used to analyse the early mortality risk in subject groups achieving lactate clearance target only, ScvO2 target only, both targets, and not achieving any target in 6 hours after onset of resuscitation adjusted for number of organ dysfunction. Results: subjects consisted of 268 patients. There were significant differences in the mortality risk between subjects who achieved both targets with subjects who achieved ScvO2 target only (adjusted hazard ratio [aHR] 13.47; 95% confidence interval [CI] 5.17-35.08) and subjects who not achieve any target (aHR 16.12; 95%CI 7.43-34.95). There were insignificant difference the early mortality risk between subjects who achieved both targets with subjects achieved lactate clearance target only (aHR 2.29; 95%CI 0.83-6.32). Conclusion: in patients with sepsis and septic shock, achievement of lactate clearance and ScvO2 targets associates with similar early mortality risk compared to achievement of lactate clearance target only. However, it associates with lower early mortality risk compared with ScvO2 target only.